Some Observations on the Carbon Dioxide Burst in Chlorella and Chlamydomonas - Bunt, J. S. (1970)
In the course of mass spectrometer studies with the algae Chlorella and Chlamydomonas, data were obtained which indicate that the CO(2) burst and gulp are sensitive to oxygen. Furthermore, the CO(2) burst was found to be strongly suppressed when wave lengths shorter than 460 nanometers were blocked at intensities adequate to saturate photosynthesis. Under appropriate conditions at 30°, the CO(2) burst was interrupted by a brief CO(2) gulp and the post illumination gulp by a brief burst of CO(2). The post illumination gulp of CO(2) could be induced during illumination by interposition of a filter blocking wave lengths shorter than 460 nanometers. These data are discussed in relation to earlier reports of the phenomenon and briefly as they affect the detection of photorespiration.